Synthesis and characterization of gold nanorods coated by mesoporous silica MCM-41 as a platform for bioapplication in photohyperthermia. (11th October 2021) - Meireles, Isabela Barreto da Costa Januário; Cipreste, Marcelo Fernando; Gastelois, Pedro Lana; Macedo, Waldemar Augusto de Almeida; Gomes, Dawidson Assis; de Sousa, Edésia Martins Barros
Abstract: Gold nanoparticles have been widely investigated for biomedical applications due to their optical properties. These particles present the interesting feature of absorbing light when stimulated with laser radiation to generate heating. Among the possible morphologies for synthetic gold nanoparticles, gold nanorods have properties of great interest for applications in the photohyperthermia processes. Due to their morphology, gold nanorods can absorb light at longer wavelengths comprising specific regions of the electromagnetic spectrum, such as the region of the biological window, in which laser radiation has less interaction with tissues. However, these nanoparticles present limitations in biomedical applications, such as low colloidal and thermal stabilities that can be overcome by coating the gold nanorods with silica MCM-41. The silicate covering can provide greater stability for gold nanorods and allow multifunctionality in treating different diseases through photohyperthermia. This work developed a specific chemical route through seed and growth solutions to synthesize gold nanorods with controlled particle size, rod morphology, and silica covering for photohyperthermia applications. The synthesized samples were characterized through a multi-technique approach that successfully demonstrated the presence of gold nanorods inside the silica coating, presenting high stability and desirable textural and morphological characteristics for bioapplications. Furthermore, silica-coated gold nanorods exhibit high biocompatibility and great performance in generating therapeutic heating by absorbing laser radiation in the biological window range, making the system developed in this work a promising agent in photohyperthermia.